Metabolome Analysis Identified Okaramines in the Soybean Rhizosphere as a Legacy of Hairy Vetch - Sakurai, Nozomu; Mardani-Korrani, Hossein; Nakayasu, Masaru; Matsuda, Kazuhiko; Ochiai, Kumiko; Kobayashi, Masaru; Tahara, Yusuke; Onodera, Takeshi; Aoki, Yuichi; Motobayashi, Takashi; Komatsuzaki, Masakazu; Ihara, Makoto; et al. (Frontiers in Genetics, 2020)
Inter-organismal communications below ground, such as plant–microbe interactions in the rhizosphere, affect plant growth. Metabolites are shown to play important roles in biological communication, but there still remain a large number of metabolites in soil to be uncovered. Metabolomics, a technique for the comprehensive analysis of metabolites in samples, may uncover the molecules that intermediate these interactions. We conducted a multivariate analysis using liquid chromatography (LC)—mass spectrometry (MS)-based untargeted metabolomics in several soil samples and also targeted metabolome analysis for the identification of the candidate compounds in soil. We identified okaramine A, B, and C in the rhizosphere soil of hairy vetch. Okaramines are indole alkaloids first identified in soybean pulp (okara) inoculated with Penicillium simplicissimum AK-40 and are insecticidal. Okaramine B was detected in the rhizosphere from an open field growing hairy vetch. Okaramine B was also detected in both bulk and rhizosphere soils of soybean grown following hairy vetch, but not detected in soils of soybean without hairy vetch growth. These results suggested that okaramines might be involved in indirect defense of plants against insects. To our knowledge, this is the first report of okaramines in the natural environment. Untargeted and targeted metabolomics would be useful to uncover the chemistry of the rhizosphere.